Influence of the microstructure on the creep behaviour of Tin-Silver-Copper solder - Ribeiro, Pedro Emanuel Abreu (2018)
A common failure mode of electronic printed circuit boards (PCB’s) is the appearance of cold solder joints between the component and PCB, during product life. This phenomenon is related to solder joint fatigue and is attributed mainly to the mismatch of the coefficients of thermal expansion (CTE) of component-solder-PCB assembly. With today’s solder joint thickness decreasing and increasing working temperatures, among others, the stresses and strains due to temperature changes are growing, leading to limited fatigue life of the products. As fatigue life decreases with increasing plastic strain, creep occurrence should have significant impact, especially during thermal cycles and, thus, should be studied. Through the cooling phase, on the production of PCB assembly’s by the reflow technology, the hoven atmosphere temperature is adjusted in order to control the cooling rate. Narrow criteria is used so as to control the inter-metallic compounds (IMC) thickness, PCB assembly distortion and defects due to thermal shock. The cooling rate also affects solder microstructure, which has direct impact on creep behaviour and, thus, on the soldered joint reliability. In this paper, a dynamic mechanical analyser (DMA) is used to study the influence of the solder cooling rate on its creep behaviour. SAC405 samples with two distinct cooling rates were produced: inside a hoven cooling and by water quenching. Creep tests were made on three-point-bending clamp configuration, isothermally at 25 °C, 50 °C and 75 °C and under three separate levels of stress, 3, 5 and 9 MPa. The results show that creep behaviour has a noticeable cooling rate dependence. It was also noticed that creep propensity is exacerbated by the temperature at which stresses are applied, especially for the slower cooling rates. Creep mechanisms were related to the solder microstructural constituents, namely by the amount of phases ant their morphology.